Characterization of the first mitogenomes of the smallest fish in the world, Paedocypris progenetica, from peat swamp of Peninsular Malaysia, Selangor, and Perak - Hussin, NorJasmin; Azmir, Izzati Adilah; Esa, Yuzine; Ahmad, Amirrudin; Mohd Salleh, Faezah; Jahari, Puteri Nur Syahzanani; Munian, Kaviarasu; Gan, Han Ming (Korea Genome Organization, 2022)
The two complete mitochondrial genomes (mitogenomes) of Paedocypris progenetica, the smallest fish in the world which belonged to the Cyprinidae family, were sequenced and assembled. The circular DNA molecules of mitogenomes P1-P. progenetica and S3-P. progenetica were 16,827 and 16,616 bp in length, respectively, and encoded 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and one control region. The gene arrangements of P. progenetica were identical to those of other Paedocypris species. BLAST and phylogenetic analyses revealed variations in the mitogenome sequences of two Paedocypris species from Perak and Selangor. The circular DNA molecule of P. progenetica yield a standard vertebrate gene arrangement and an overall nucleotide composition of A 33.0%, T 27.2%, C 23.5%, and G 15.5%. The overall AT content of this species was consistent with that of other species in other genera. The negative GC-skew and positive AT-skew of the control region in P. progenetica indicated rich genetic variability and AT nucleotide bias, respectively. The results of this study provide genomic variation information and enhance the understanding of the mitogenome of P. progenetica. They could later deliver highly valuable new insight into data for phylogenetic analysis and population genetics.